The Recognition of Solid Object Shape: The Importance of Inhomogeneity. (August 2019) - Norman, J. Farley; Wheeler, Sydney P.; Pedersen, Lauren E.; Shain, Lindsey M.; Kinnard, Jonathan D.; Lenoir, Joel
A single experiment evaluated the haptic-visual cross-modal matching of solid object shape. One set of randomly shaped artificial objects was used (sinusoidally modulated spheres, SMS) as well as two sets of naturally shaped objects (bell peppers, Capsicum annuum and sweet potatoes, Ipomoea batatas ). A total of 66 adults participated in the study. The participants' task was to haptically explore a single object on any particular trial and subsequently indicate which of 12 simultaneously visible objects possessed the same shape. The participants' performance for the natural objects was 60.9 and 78.7 percent correct for the bell peppers and sweet potatoes, respectively. The analogous performance for the SMS objects, while better than chance, was far worse (18.6 percent correct). All of these types of stimulus objects possess a rich geometrical structure (e.g., they all possess multiple elliptic, hyperbolic, and parabolic surface regions). Nevertheless, these three types of stimulus objects are perceived differently: Individual members of sweet potatoes and bell peppers are largely identifiable to human participants, while the individual SMS objects are not. Analyses of differential geometry indicate that these natural objects (e.g., bell peppers and sweet potatoes) possess heterogeneous spatial configurations of distinctly curved surface regions, and this heterogeneity is lacking in SMS objects. The current results therefore suggest that increases in surface structure heterogeneity facilitate human object recognition.